Work status, work hours and health in women with and without children. Issue 10 (29th June 2009) - Floderus, B; Hagman, M; Aronsson, G; Marklund, S; Wikman, A
Abstract : Objectives: The authors studied self-reported health in women with and without children in relation to their work status (employed, student, job seeker or homemaker), work hours and having an employed partner. Methods: The study group comprised of 6515 women born in 1960–1979 who were interviewed in one of the Swedish Surveys of Living Conditions in 1994–2003. Self-rated health, fatigue and symptoms of anxiety were analysed. Results: Having children increased the odds of poor self-rated health and fatigue in employed women, female students and job seekers. The presence of a working partner marginally buffered the effects. In dual-earner couples, mothers reported anxiety symptoms less often than women without children. Few women were homemakers (5.8%). The odds of poor self-rated health and fatigue increased with increasing number of children in employed women, and in women working 40 h or more. Poor self-rated health was also associated with the number of children in students. Many mothers wished to reduce their working hours, suggesting time stress was a factor in their impaired health. The associations between having children and health symptoms were not exclusively attributed to having young children. Conclusions: Having children may contribute to fatigue and poor self-rated health particularly in women working 40 h or more per week. Student mothers and job seeking mothers were also at increased risk of poor self-rated health. The results should be noted by Swedish policy-makers. Also countries aiming for economic and gender equality should consider factors that may facilitate successful merging of work and family life.